Interaction experience in field work in a Colombian rural zone - Arias Valencia, María Mercedes (Investigación y Educación en Enfermería, 2011)
<!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> The field work experience as a researcher with Ember Chamí Indians in the city of Jardín Antioquia, Colombia is shared. Work field implications, participants’ approach as individuals, groups or communities and societies. It tells specifically the introduction, field orientation, interaction with people, rule observation, daily, weekly and monthly life organization, as well as the roles and reciprocity relationships in the field.